2014
DOI: 10.1590/0104-6632.20140314s00003087
|View full text |Cite
|
Sign up to set email alerts
|

Nanofiltration: ion exchange system for effective surfactant removal from water solutions

Abstract: -A system combining nanofiltration and ion exchange for highly effective separation of anionic surfactant from water solutions was proposed. The subjects of the study were nanofiltration polyethersulfone membranes and ion-exchange resins differing in type and structure. The quality of the treated solution was affected by numerous parameters, such as quality of the feed solution, membrane cut-off, resin type, dose and the solution contact time with the resin. A properly designed purification system made it poss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…For example, physical pretreatments such as microfiltration (MF), ultrafiltration (UF), or nanofiltration (NF) can effectively remove amphiphilic proteins that may eventually wet the pores of a hydrophobic membrane. , However, they cannot mitigate pore wetting induced by surfactants or LST water-miscible liquids. Surfactants can be removed from solution via ion exchange, coagulation, , floatation or foam fractionation, or biodegradation. , While some of the aforementioned pretreatment methods have not yet been tested for MD or MC and a knowledge gap exists in matching the appropriate pretreatment method given a real water application, some studies have shown promise in using these pretreatment strategies for MD and MC. For example, dispersing bubbles into a surfactant-containing feed solution from the textile industry formed floating foams that removed surfactants from the bulk solution.…”
Section: Pore Wettingmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, physical pretreatments such as microfiltration (MF), ultrafiltration (UF), or nanofiltration (NF) can effectively remove amphiphilic proteins that may eventually wet the pores of a hydrophobic membrane. , However, they cannot mitigate pore wetting induced by surfactants or LST water-miscible liquids. Surfactants can be removed from solution via ion exchange, coagulation, , floatation or foam fractionation, or biodegradation. , While some of the aforementioned pretreatment methods have not yet been tested for MD or MC and a knowledge gap exists in matching the appropriate pretreatment method given a real water application, some studies have shown promise in using these pretreatment strategies for MD and MC. For example, dispersing bubbles into a surfactant-containing feed solution from the textile industry formed floating foams that removed surfactants from the bulk solution.…”
Section: Pore Wettingmentioning
confidence: 99%
“…63,64 However, they cannot mitigate pore wetting induced by surfactants or LST water-miscible liquids. Surfactants can be removed from solution via ion exchange, 65 coagulation, 66,67 floatation or foam fractionation, 68−70 or biodegradation. 71,72 While some of the aforementioned pretreatment methods have not yet been tested for MD or MC and a knowledge gap exists in matching the appropriate pretreatment method given a real water application, some studies have shown promise in using these pretreatment strategies for MD and MC.…”
Section: ■ Pore Wettingmentioning
confidence: 99%
“…The data processing required manual reduction, but after verification of the homologous series tool, further analysis should be less time consuming. Regarding water treatment, hydrocarbon surfactants in AFFF-contaminated groundwater can compete with PFASs for ion-exchange sites on resins, on granulated activated carbon, and for oxidants during in situ chemical oxidation . AFFF-impacted groundwater discharges into surface waters where the hydrocarbon surfactants have the potential to contribute to foaming and biodegrade aerobically to transformation products that might have the potential to adversely impact biota.…”
Section: Resultsmentioning
confidence: 99%
“…Boussu et al (2007) [27] observed a decrease in relative fluxes of the hydrophilic membrane Desal51HL as initial concentration of the anionic and cationic surfactants sodium dodecylbenzenesulfonate (SDBS) and cetrimide increased from 20 to 70 mg L −1 , at pH 6. In addition, Kowalska (2014) [45] evaluated the application of the nanofiltration-ion exchange system for removing surfactants from water, and as initial SDBS concentration increased in the feed solution from 1.3 to145 mg L −1 for NP010 membrane and from 1.2 to 106 mg L −1 for NP030 membrane, the permeabilities of these membranes were decreased [45].…”
Section: Permeate Flux Of the Mixture Ctab And Sds By The Nf90 Membranementioning
confidence: 99%